2015
DOI: 10.1016/j.aap.2015.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Operating under the influence: Three year recidivism rates for motivation-enhancing versus standard care programs

Abstract: Operating a motor vehicle under the influence of alcohol (OUI) is an international problem. In the United States, one intervention strategy is to require offenders to attend group-delivered interventions. We compared three year rearrest rates among 12,267 individuals in Maine receiving either a motivation-enhancing (ME) program, Prime For Life(®), or historical standard care (SC) programs. We created two cohorts, one when Maine used SC (9/1/1999-8/31/2000) and one after the ME program was implemented (9/1/2002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…A previous data collection showed PFL to be effective in producing short-term changes in cognitive outcomes [23]. Another study showed that such changes are meaningful and translate into longer-term improvements: in an examination of driving records of PFL attendees in a 2-day version of the program, PFL participants had lower 3-year recidivism rates compared to standard care conditions [24]. In both datasets, changes occurred for emerging adults as well as the broader range of adult participants.…”
Section: Introductionmentioning
confidence: 99%
“…A previous data collection showed PFL to be effective in producing short-term changes in cognitive outcomes [23]. Another study showed that such changes are meaningful and translate into longer-term improvements: in an examination of driving records of PFL attendees in a 2-day version of the program, PFL participants had lower 3-year recidivism rates compared to standard care conditions [24]. In both datasets, changes occurred for emerging adults as well as the broader range of adult participants.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with prior research demonstrating the efficacy of PFL as an indicated prevention program, we hypothesized that participants overall would show significant pre–post program improvements in risk perception and behavioral intentions. However, we considered analyses of potential age differences in magnitude of change during the program and status at program completion to be exploratory, given the mixed findings from prior research about age differences on the impact of motivational enhancement‐based DUI programs, including PFL (Beadnell et al, , ; Ouimet et al, )…”
Section: The Current Studymentioning
confidence: 99%
“…First, in an analysis of pre–post evaluation data from 522 individuals convicted of a substance‐related offense in North Carolina, Beadnell et al () showed that PFL produced greater short‐term changes in knowledge, perceived substance‐related risk, and problem recognition than intervention as usual. And second, in an evaluation study in the state of Maine ( N = 12,267), Beadnell, Crisafulli, Stafford, Rosengren, and DiClemente () showed that the 3‐year rearrest rate among drivers who attended PFL after a DUI arrest was lower than the rate for drivers receiving standard educational programs.…”
mentioning
confidence: 99%
See 2 more Smart Citations